Usefulness of diurnal trunk shrinkage as a water stress indicator in plum trees - Intrigliolo, Diego S.; Castel, Juan R. (2017)
We compared seasonal changes in maximum diurnal trunk shrinkage (MDS) with seasonal changes in midday stem water potential (Psi(s)) over three years in plum trees grown in differing drip-irrigated regimes. In well-irrigated trees, day-to-day variations in Psi(s) and MDS were related to evaporative demand. Reference equations were obtained to predict MDS and Psi(s) values for well-irrigated trees as functions of environmental conditions. A decrease in plant water status toward the end of the growing season occurred even in the well-irrigated trees, probably reflecting a reduced volume of soil wetted by the drip irrigation system. Thus, for the prediction of Psi(s), different reference equations are required for the fruit-growth and after-harvest phenological periods. A seasonal change in the relationship between MDS and Psi(s) was observed, which compensated for the decrease in plant water status such that well-irrigated trees had similar MDS values during both the fruit-growth and after-harvest periods. The influence of tree size on the relationship between MDS and Psi(s) was also investigated. For tree trunk diameters ranging between 8 and 13 cm, MDS increased 13% for each cm of increase in trunk diameter, as a result of the thicker phloem tissues of the larger trees. This finding may allow extrapolation of Psi(s) predictions based on empirical relationships with MDS to plum trees of different sizes.